A new spatio-temporal wave based target tracking algorithm - Yeniceri, Ramazan; Kilic, Volkan; Yalcin, Mustak (IEEE, 2010)
In this paper, the model and implementation of a Cellular Nonlinear Network which is able to solve the shortest path finding problem between two points in a two dimensional space including obstacles is presented with a navigation algorithm towards the target via the shortest path. Then, the target tracking scenario with tracker and target robots on a platform which is specially prepared for this application is realized using mentioned algorithm.